Cymbal and BB flat panel and conformal sonar arrays - Newnham, RE; Hughes, WJ; Markley, DC; Meyer, RJ Jr; Alkoy, S; Hladkey-Hennion, AC; Zhang, JD (Compass Publications, Inc, 2002)
[No abstract available]